SISTEM PENYALURAN GAS ELPIJI KE AGEN PADA SPPBE PT. PURI KENCANA MERDEKA UTAMA SEMARANG BERBASIS WEB - Adi, Triatmojo; Eko Nur, Wahyudi (Information Technology and Telematics, 2018)
Abstract- SPPBE PT. Puri Kencana Merdeka Utama Semarang does a lot of work such as registering the amount of gas to be distributed, registering the number of customers, conducting gas distribution transactions and making reports needed by the manager, where in carrying out his work, employees sometimes find difficulties and errors, such as difficulty finding customer data, customer data collection processes that take a long time, miscalculating the amount of selling prices, insecure data storage and less effective reporting process.The system development method used in this research is Waterfall which consists of requirement definition, system and software design using DFD and ERD, implementation using PHP and MySQL. The final result of this research is a LPG distribution systems to agents in SPPBE PT. Puri Kencana Merdeka Main Semarang web-based can be used to assist the administration in processing LPG filling information where the administration section only input data only and the processing is carried out by the computer so it will reduce errors that usually occur in the manual system